Assessing the impact of Thailand government policies and programs in local context the case study of Karen's Baan Huai Hin Lad Nai - Macalib-og, Ariane Lou D.; Macalib-og, Ariane Lou D.
This qualitative research attempts to shed light on Thai policies and programs addressing indigenous people's condition in Northern Thailand since 2007 and to assess its impact on a local Karen case community. It aims to answer the main question : since the Thai ratification of UNDRIP in 2007, what has been the impact of government policies and programs on the Karen ethnic community residing in Baan Huai Hin Lad Nai? This research uses the theory of Modernity in the analysis of the Thai state policies and programs on indigenous people in the North and its impact on a Karen case community. Modernity provides the key concepts of integration or assimilation or incorporation of the periphery into the center as part of the formation of a modern nation-state, which involves inculcating nationalism on a historical, political, and cultural diverse population in order to achieve a unified national Thai identity. The conceptual pattern is used to describe the integration mechanism and to analyze the relationship between the Thai (center) and the Northern hill tribes or Chao Khao (periphery). The study argues that all policies and programs implemented for the ethnic groups in northern Thailand and its impact in a local community are all part of the continuous and strengthened integration process of the ethnic groups into Thai-centric society. The study focused on the Thai government policies and programs to the Northern hill tribes since 2007 that were categorized as sociocultural and economic. The sociocultural policies and programs were the Nationality Act and Education for all the recognized ethnic groups in the North. Once nationality is proven, ethnic communities gain access to all government services and benefits. Education is the best means and venue for sociocultural assimilation of the minorities to embody Thai national identity. Economic policies and programs were mostly providing agricultural assistance. Since all of the villagers are farmers and the villages is located within the forest, the Ministry of Agriculture and Forestry actively gives assistance and monitors the environmental activities in the areas. The study found out that the impact of Thai government policies and programs on the Karen community in Baan Huai Hin Lad Nai can be characterized as following two patterns. First is the patterns of adaptation of the Karen village to the Thai sociocultural and economic initiatives. They were able to cope with and adapt to the government assimilation initiatives in education and by becoming citizens. They learned that Thai language, converted to Buddhism, and became loyal to the monarch. The Karen community has come to embody Thai-ness and loyalty to the nation-state. Secondly, the patterns of continuity were evident despite the Thai government's consistent and strengthened efforts since the 19th century to assimilate the ethnic group. The Karen case community displayed an impressive continuity of distinctive traditional and cultural practices. They were able to maintain practical and traditional animist beliefs in agriculture and still speak the Karen language. On one hand, they were able to protect and maintain their identity covertly while adapting to the mainstream Thai-centric culture and national identity.